(untitled) - Rishel, James B. (New York, 2002)
AN ESSENTIAL DESKTOP SOURCEBOOK FOR ANYONE WHO WORKS WITH PUMPS AND PUMPING SYSTEMS ON A DAILY BASIS This much-needed reference provides comprehensive, detailed coverage of pump application and pumped water systems as well as a sound working overview of pump design. Written by a hands-on expert with almost fifty years in the field, Water Pumps and Pumping Systems thoroughly examines: * NFPA Fire Standards * Potable and wastewater pumps * Installation, operation, and retrofit * Piping system calculations and friction analysis * Piping materials * Fire, municipal, domestic, water treatment, and industrial applications * Tools of design and design analysis * Performance issues * And more
Keywords: Sewerage disposal,Hydraulic engineering,Water reuse